Removal of Pb(II) ions by adsorption from aqueous solutions using beans peel powder as a new adsorbent - Habib, Hassan Abbas; Alwan, Salam H. (Al-Qadisiyah Journal of Pure Science, 2017)
In the present study, beans peel was used as an adsorbent for removing Pb(II) ions from aqueous solutions. The amounts of adsorbed ions were estimated were carried out by using flame atomic absorption spectrophotometer. The effects of initial metal ions concentration, pH , existing salt and temperature were studies. The adsorption isotherms are of H-curve type according to Giles classification and the experimental data were best fitted to Langmuir and Freundlich isotherm models. The adsorption phenomenon was examined as a function of temperature (20,30, 40 and 50oC) and various thermodynamic parameters (ï„Ho, ï„So and ï„Go) have been calculated. The thermodynamic parameters of lead ion- beans peel systems indicated the adsorption processes is spontaneous. The results indicated that the adsorption extent of lead ions onto beans peel increased with increasing the pH of solution and it was decreased with increasing ionic strength of solution.